Promotion of osteointegration under diabetic conditions by a silk fibroin coating on 3D-printed porous titanium implants via a ROS-mediated NF-κB pathway. (1st March 2021) - Ma, Xiang-Yu; Ma, Tian-Cheng; Feng, Ya-Fei; Xiang, Geng; Lei, Wei; Zhou, Da-Peng; Yu, Hai-Long; Xiang, Liang-Bi; Wang, Lin
Abstract: Clinical evidence indicates the compromised application of titanium implants (TIs) in diabetics, associated with reactive oxygen species (ROS) overproduction at the bone-implant interface. Silk fibroin (SF) has displayed impressive biocompatibility in the application of biomedical material and optimal anti-diabetic effects in oriental medicine. We proposed that SF-coated titanium implants (STIs) could alleviate diabetes-induced compromised osteointegration, which has rarely been reported before. To confirm this hypothesis and explore the underlying mechanisms, rat osteoblasts cultured on 3-dimensional (3D) -printed titanium implants (TIs) and STIs were subjected to normal serum (NS), diabetic serum (DS), DS with N-acetyl-L-cysteine (a ROS inhibitor) or SN50 (an NF-κB inhibitor). An in vivo study was performed on diabetic sheep with TIs or STIs implanted into bone defects on the crista iliaca . The results demonstrated that ROS overproduction induced by diabetes lead to osteoblast dysfunctions and cellular apoptosis on the TI substrate, associated with the activation of an NF-κB signaling pathway in osteoblasts. Importantly, the STI substrate significantly attenuated ROS production and NF-κBp65 phosphorylation, thereby ameliorating the osteoblast biological dysfunctions. These results were further confirmed in vivo by the improved osteointegration of the STIs, as evidenced by Micro-CT and histological examinations compared with those of TIs. These results demonstrated that the ROS-mediated NF-κB signaling pathway played a crucial role in diabetes-induced implant destabilization. Importantly, the SF coating, as a promising material for biomaterial-engineering, markedly improved the clinical treatment effect of TIs under diabetic conditions, possibly associated with the suppression of the NF-κB pathway.